The key to Zion - Thoene, Bodie, 1951- (Thoene, Bodie, 1951- Zion chronicles, 2006)
The British are in the final stages of their military evacuation from Palestine. While the Jewish Haganah trains its pilots in fighters, Moshe is still trying to supply the Old City of Jerusalem with food.